Τηλεχειρισμός τροχοφόρου ρομπότ από ρομποτικό βραχίονα μέσω οπτικής ανατροφοδότησης βασισμένη σε εικόνα από οθόνη - Λογοθέτης, Μιχαήλ (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών, 2016)
In this work, the tele-operation problem of a mobile robot via a mobile - manipulator system is studied. To contribute to this problem, an image-based visual servo control scheme is proposed. The robot-operator robotic system is equipped with a camera, which is monitoring a screen, to acquire the visual data and having grasped a joystick, it accomplishes the teleoperation task. On the other hand, the mobile robot consists of a holonomic robot platform and a camera whose acquired vision data is displayed on the screen. Since the camera intrinsic parameters of the mobile robot, the relative position between the mobile robot and the target and the accurate value of the mobile robot’s spatial velocity are unknown, it is necessary to develop a control scheme that controls the joystick movements in order to achieve the goal. Finally, an extensive experimental study clarifies and verifies the theoretical findings.